2013
DOI: 10.3168/jds.2012-5794
|View full text |Cite
|
Sign up to set email alerts
|

Change in subcutaneous adipose tissue metabolism and gene network expression during the transition period in dairy cows, including differences due to sire genetic merit

Abstract: Adipose metabolism is an essential contributor to the efficiency of milk production, and metabolism is controlled by several mechanisms, including gene expression of critical proteins; therefore, the objective of this study was to determine how lactational state and the genetic merit of dairy cattle affects adipose tissue (AT) metabolism and mRNA expression of genes known to control metabolism. Animals of high (HGM) and low genetic merit (LGM) were fed to requirements, and weekly dry matter intake, milk produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
53
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 40 publications
(68 reference statements)
14
53
2
3
Order By: Relevance
“…This is in agreement with other studies reporting that proteins involved in lipid metabolism are mostly increased in adipose tissue in IR states. [11][12][13][14] The specific role of several novel proteins that were differentially expressed in the IR adipose of dairy cows is discussed below.…”
Section: Protein Expression In Ir Vs Is Adipose Tissuementioning
confidence: 99%
“…This is in agreement with other studies reporting that proteins involved in lipid metabolism are mostly increased in adipose tissue in IR states. [11][12][13][14] The specific role of several novel proteins that were differentially expressed in the IR adipose of dairy cows is discussed below.…”
Section: Protein Expression In Ir Vs Is Adipose Tissuementioning
confidence: 99%
“…However, the degree of fat mobilization and whether the cow goes into a negative energy balance varies from cow to cow (Bell, 1995;Grummer, 1995;Goff, 2006;Khan et al, 2013;Rocco and McNamara, 2013;Weber et al, 2013). The hallmark of the dairy cow's negative energy balance is mobilizing fat from body stores as NEFA to utilize for energy.…”
Section: Introductionmentioning
confidence: 98%
“…Although McNamara and Hillers (1986) showed that cows with higher genetic merit for milk production mobilize more fat in early lactation, their study did not evaluate the influence of Ca status. More recently, Khan et al (2013) showed that basal and stimulated lipolysis were greater in high-genetic-merit cows at 7 DIM; however, by 28 DIM, no differences were observed when compared with low-genetic-merit cows. It is also possible that the milk production measures used in the present study (peak test-day milk yield and 305-d mature-equivalent 4% FCM) were not sensitive enough to detect subtle differences in production during early lactation.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Diet composition and plan of nutrition, parity and milk yield strongly influence the extent of AT accumulation and losses and it has been observed that also genetic merit of the cow can influence the mobilization of fat depots (Sgorlon et al, 2015a). Adipose tissue mass is determined by balancing lipolysis, lipogenesis, and adipocyte proliferation (Della-Fera et al, 2001) and it is likely that genetic make-up of the animal regulates the nutrient fluxes among tissues and modulates the expression of genes which orchestrate the metabolism and the fate of adipose cells (Khan et al, 2013;Rocco and McNamara, 2013).…”
Section: Introductionmentioning
confidence: 99%